The Influence of the Performance of Implementing Nurses and Compliance with the Phlebitis Bundle Documentation on the Incident of Phlebitis in the Inpatient Room of the Kediri District Hospital - Chosmas Efendi; Sentot Imam Suprapto; Joko Prasetyo (Universitas STRADA Indonesia, 2026)
Infections acquired by patients in health care facilities are a serious problem for health service providers. This incident is called Health Care Associated Infections (HAIs). How to prevent it by Bundle HAIs Phlebitis. Implementation requires a protocol in the form of documentation that is useful in performance assessment. Research objective: to determine the effect of implementing nurses' performance and documentation compliance bundle phlebitis to the incident phlebitis at the Kediri District Hospital. Types of research : observational quantitative with cross sectional design. A population of 340 nurses with 148 research samples was used random sampling, including inclusion and exclusion criteria.